Инновационная методологическая платформа развития личности в информационном образовательном пространстве - Берулава , Галина А.; Берулава, Михаил Николаевич (International Dialogues on Education Journal, 2014)
Current higher-eduction systems are characterized by an absolute crisis of an outdated methodological paradigm. Therefore the continuation of „test-tube studies“ of individual „fragments“ of human beings, without reference to new methodologicla realities, has no prospects. At the same time, the dominat model of the university, prevalant for 200 years, remains unaltered. Today, however, the aims, means and players of socialization are changing. This article proposes and discusses a new methodological basis for personality development from the perspective of an behavioural-therapeutic approach is. The role of behaviour patterns is portrayed in the context of social and professional personality successes.